Hubungan antara intensitas penggunaan Instagram dengan pemenuhan kebutuhan informasi promo followers @giladiskonn - Habibaturrahmah Habibaturrahmah; Edwin Rizal; Rully Khairul Anwar (Jurnal Informatio, 2022)
This article discusses the relationship between the intensity of Instagram uses and the fulfillment of promo information needs of followers of @giladiskonn Instagram account. This study aimed to describe the relationship between the intensity of Instagram use and the fulfillment of the needs of followers' promo information on @giladiskonn Instagram account. The quantitative method uses a correlational approach using Pearson Product Moment correlation calculations. The sample of this research was as many as 100 respondents selected using probability sampling with a simple random sampling technique. Data collection techniques used are online questionnaires, observations, and literature studies. A validity test using Pearson Product Moment and a reliability test using Cronbach Alpha were conducted to test the data. This research uses the theory of Uses and Gratifications and Information Needs. The results showed that there is a low correlation between the Intensity of Instagram Use and the Cognitive Needs of followers, a moderate correlation between the Intensity of Instagram Use and the Affective Needs of followers, a moderate correlation between the Intensity of Instagram Use and Personal Needs in an Integrative Followers, a moderate correlation between Intensity of Use and Social Needs integrative followers. There is a relationship with a moderate correlation between the intensity of Instagram use and the entertainment needs of followers. So, there is a relationship between the intensity of Instagram use and the fulfillment of the promotional information needs of followers which means that Instagram is needed to meet the needs of promotional information of @giladiskonn followers.